2003
DOI: 10.1152/ajpregu.00065.2002
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of nitric oxide and prostaglandins on renal escape from vasopressin-induced antidiuresis

Abstract: Recent results from our laboratories indicate that renal escape from AVP-induced antidiuresis is accompanied by marked downregulation of kidney aquaporin-2 (AQP2) and AVP V2 receptors. The present studies evaluated the effect of nitric oxide (NO) and PG synthesis blockade on escape from antidiuresis. dDAVP-infused rats were water loaded (WL) for 5 days. l-NAME, an NO synthesis inhibitor, or diclofenac, a cyclooxygenase inhibitor, was infused subcutaneously beginning 1 day before WL. As early as 2 days after WL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…On the other hand, AVP infusion stimulates aquaporin-2 apical membrane expression in renal collecting ducts under physiological conditions, although modulation of this process after endotoxin challenge is unknown. "Vasopressin escape" from antidiuresis has been described in animals after several days of drug infusion and is related (6) to a marked AVP-independent decrease in kidney aquaporin-2 mRNA and protein expression as well as AVP V2 receptor binding (18,29). In this study natriuresis did not increase after endotoxin challenge and AVP infusion, but the experimental period was very short.…”
Section: Effects Of Drug Treatment On Diuresis and Renal Functionmentioning
confidence: 57%
“…On the other hand, AVP infusion stimulates aquaporin-2 apical membrane expression in renal collecting ducts under physiological conditions, although modulation of this process after endotoxin challenge is unknown. "Vasopressin escape" from antidiuresis has been described in animals after several days of drug infusion and is related (6) to a marked AVP-independent decrease in kidney aquaporin-2 mRNA and protein expression as well as AVP V2 receptor binding (18,29). In this study natriuresis did not increase after endotoxin challenge and AVP infusion, but the experimental period was very short.…”
Section: Effects Of Drug Treatment On Diuresis and Renal Functionmentioning
confidence: 57%
“…Inhibition of nitric oxide and prostaglandin synthesis was able to increase aquaporin 2 level and therefore avoid the vasopressin escape phenomenon (24). Several experimental studies have indicated that angiotensin II (AngII) can increase V 2 R expression, so the low AngII concentration observed in SIADH could contribute to the escape (25).…”
Section: Urine Osmolalitymentioning
confidence: 99%
“…However, it is now clear that vasopressin-independent pathways also play a role, since decreases in AQP2 are seen in association with the ability to lose water in the urine despite ongoing vasopressin infusion (vasopressin escape phenomenon) (8,9). This escape phenomenon has been shown to depend on both nitric oxide and prostaglandin production (26). There is evidence that tonicity may be a significant signal (16,19).…”
mentioning
confidence: 99%